2018
DOI: 10.1021/acs.organomet.8b00254
|View full text |Cite
|
Sign up to set email alerts
|

Deca-Arylsamarocene: An Unusually Inert Sm(II) Sandwich Complex

Abstract: Samarocene sandwich complexes with superbulky penta-arylcyclopentadienyl ligands have been prepared and were structurally characterized: [(4-EtC 6 H 4 ) 5 C 5 ] 2 Sm (1) and [(4-iPrC 6 H 4 ) 5 C 5 ] 2 Sm (2). Analogous to the previously reported synthesis of [(4-nBuC 6 H 4 ) 5 C 5 ] 2 Sm, reaction of (DMAT) 2 Sm• (THF) 2 (DMAT = 2-Me 2 N-α-Me 3 Si-benzyl) and the appropriate Ar 5 C 5 H ligand gave 1 (66% yield) and 2 (59% yield). In contrast to the high reactivity of Cp* 2 Sm, complex 1 has been shown to be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 64 publications
2
25
0
Order By: Relevance
“…Sandwich or half‐sandwich complexes incorporating penta‐arylcyclopentadienyl ligands exist across the Periodic Table . The suitable selection of an aryl group (Ar=4‐R‐C 6 H 4 , R=Me, Et, i Pr, n Bu; Ar=3,5‐R 2 C 6 H 3 , R=Me, t Bu) for substitutions on the C 5 carbocycle has led to the corresponding complexes with improved solubility and better crystallinity. Previously, Harder et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sandwich or half‐sandwich complexes incorporating penta‐arylcyclopentadienyl ligands exist across the Periodic Table . The suitable selection of an aryl group (Ar=4‐R‐C 6 H 4 , R=Me, Et, i Pr, n Bu; Ar=3,5‐R 2 C 6 H 3 , R=Me, t Bu) for substitutions on the C 5 carbocycle has led to the corresponding complexes with improved solubility and better crystallinity. Previously, Harder et al.…”
Section: Methodsmentioning
confidence: 99%
“…Sandwich or half-sandwich complexes incorporating penta-arylcyclopentadienyl ligands exist across the Periodic Table. [12] Thes uitable selection of an aryl group (Ar = 4-R-C 6 H 4 ,R= Me, [13] Et, i Pr, [14] n Bu; [15] Ar = 3,5-R 2 C 6 H 3 ,R= Me, t Bu [16] )f or substitutions on the C 5 carbocycle has led to the corresponding complexes with improved solubility and better crystallinity.Previously,Harder et al reported that protonolysis of heavy alkaline-earth-metal dibenzyl complexes AeR 2 (R = benzyl) with (Cp BIG )H (Cp BIG = (4-n Bu-C 6 H 4 ) 5 -cyclopentadienyl) gave sandwich (Cp BIG ) 2 Ae,n ot the desired heteroleptic (Cp BIG )AeR complexes. [15] Inspired by these results,w ed eliberately synthesized an ew penta-arylcyclopentadienyl ligand with i Pr groups in the meta positions of the Ph rings,( Cp Ar )H (Cp Ar = C 5 Ar 5 ,A r = 3,5-i Pr 2 -C 6 H 3 )t o increase the steric hindrance.Herein, we report the synthesis and structures of (Cp Ar )Ae[CH(SiMe 3 ) 2 ](THF) (1-Ae)(Ae = Ca, Sr, Ba).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A promising method to overcome this experimental problem is the use of para-alkyl-substituted pentaarylcyclopentadienyl ligands C5(p-alkyl-Ph)5 [16][17][18][19] such as pentakis-(4-n-butylphenyl)cyclopentadienyl (Cp Big = C5(p-n-Bu-Ph)5) [16] as well as the corresponding pentakis-(4-ethylphenyl)cyclopentadienyl (C5(p-Et-Ph)5) and pentakis-(4-ipropylphenyl)cyclopentadienyl derivatives (C5(p-i-Pr-Ph)5). [20] In addition, the introduction of (bulky) substituents in para-position furthermore enhances the steric bulk of the ligand. Scheme 1: Symmetrically alkyl-substituted pentaaryland pentabenzylcyclopentadienes.…”
Section: Introductionmentioning
confidence: 99%
“…Scheme 1: Symmetrically alkyl-substituted pentaaryland pentabenzylcyclopentadienes. [13,[20][21][22][23][24][25] These sterically demanding cyclopentadienyl ligands were successfully applied in the synthesis of decaarylmetallocenes M[C5(p-R-Ph)5]2, which were found to form relatively strong "merry-go-round" hydrogen bond networks between the neighboring pentaarylcyclopentadienyl ligands, thus favoring the homoleptic and linear coordination of a metal center by two cyclopentadienyl ligands. Quantum chemical calculations at the DFT+D-level of theory showed a combined interaction energy of −87.2 kJ mol -1 for all ten hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%